(untitled) (UNED Research Journal, 2023)
“Human-wildlife conflict in a buffer zone in San Ramón, Costa Rica”. Introduction: Currently, biodiversity is mainly managed by protected areas, but proximity with human activities results in conflicts, which are poorly studied in the tropics. Objective: To estimate human-wildlife conflict in the buffer zone of the Alberto Manuel Brenes Biological Reserve, San Ramón, Costa Rica. Methods: We interviewed the owners or managers of 59 farms. Results: We recorded 540 incidents, mostly with mammals (N=479); coyotes (Canis latrans) killed 1 074 animals in 183 attacks at 12 farms. We also recorded conflicts with jaguar, Panthera onca, puma, Puma concolor, ocelot, Leopardus pardalis, and margay, Leopardus wiedii, which preyed on 261 domestic animals. Other mammals and snakes were also reported, especially the Fer-de-lance, Bothrops asper. In six occasions, the incidents took place over 500m from a house; however, most were 0-25m from a house (mean 398m). The farmers have sacrificed pumas, coyotes, raccoons and snakes and there was not a coordinated control effort from institutions, NGOs and communities. Conclusion: Coyotes are the most common wild animals involved and there is need for a coordinated effort that includes both organizations and communities.